Religião e psicanálise no Brasil contemporâneo: novas e velhas Weltanschauungen - Duarte, Luiz F. D. (2005)
The role of psychoanalysis in Brazil both as a knowledge and as an institution has changed considerably since the end of the 1970s, when its prestige in the social and cultural life of the country had reached its acme. Several recent analyses describe a growingly decentralized, diversified and complex situation; alongside a proliferation of religious and para-religious resources. That process was more obviously connected to the New Age movements, considered as typical of middle-classes, as a variant of psychological culture. The recent growth of Pentecostal sects, mostly in the lower classes, seemed to obey to other cultural premises. Yet, more recently, the emergence of an intense dialogue between Protestantism and Pentecostalism, on one side, and psychoanalysis, on the other, claimed for new research investment. Here, the research by Carvalho on that specific topic and the work by Duarte on the dynamics of religious and lay cosmologies in contemporary Brazil allow for a new integrated interpretation.